THE RELATIONSHIP BETWEEN BLOOD GLUCOSE LEVELS AND UREA LEVELS IN TYPE II DIABETES MELITUS PATIENTS AT KELAPA DUA PUBLIC HEALTH CENTER - Vivi Puspitasari Indriati; Syarah Anliza; R.A. Dewi Maria Yuliani; Rayni Anugrah; Abdallah Aleyadeh (Hypertension Prevention and Control Research Center, The Polytechnic of Health of Banten, 2026)
Type II diabetes mellitus is a chronic metabolic disease that can lead to complications, including impaired renal function. One of the initial parameters to assess these disorders is ureum level. This study aims to determine the relationship between fasting blood glucose levels and ureum levels in type II diabetes mellitus patients at Kelapa Dua Public Health Center. This study used analytic method with cross-sectional design. There were 32 people who were selected by purposive sampling and met the inclusion criteria. Blood glucose examination using the POCT method and ureum using the urease-GLDH method. Data analysis using the Spearman correlation test. Findings most respondents were female, totaling 23 people (71.9%) and most were aged between 51 and 60 years old, totaling 16 people (50.0%). Spearman correlation test showed a significant relationship between blood glucose levels and ureum levels (p = 0,001).